Analisis Peramalan dan Pengendalian Persediaan Produk Olahan Susu di Rumah Susu KUD Argopuro - Kuswardhani, Nita; Wibowo, Yuli; Yulianti, Atikah (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Rumah Susu KUD Argopuro is a sales outlet for dairy products from KUD Argopuro. The types of dairy products produced by KUD Argopuro are fresh milk, pasteurized milk, yogurt, and ice cream. This study aims to determine the demand forecasting and analyze the inventory control of dairy products at Rumah Susu KUD Argopuro. This study used the Economic Order Quantity (EOQ) method, while the forecasting analysis used the Exponential Smoothing module. The results showed that forecasting analysis used the Exponential Smoothing method with α = 0.90 in 2025 obtained quantity demand such as; fresh milk was 421072 packs with MAPE of 20.92% (adequate/reasonable); pasteurized milk was 69838 bottles with MAPE of 7.55% (very accurate); yogurt was 9734 bottles with MAPE of 15.1% (accurate); and ice cream was 14523 cups with MAPE of 15.6% (accurate). The calculation showed the optimal order quantity of fresh milk was 1508 packs with 279 order frequency and TIC of Rp4,212,227,680; pasteurized milk was 564 bottles with 124 order frequency and TIC of Rp559,153,521; yogurt was 115 bottles with 85 order frequency and TIC of Rp97,454,719; and ice cream was 271 cups with 54 order frequency and TIC of Rp58,198,765. The inventory control of dairy products that had applied the EOQ method can minimize the produce inventory costs rather than the expenses incurred by the company that did not use the EOQ method. It was found that the EOQ method was able to save Rp1,842,569,315 for the total inventory costs in 2025 or it can reduce inventory costs by 27,11%.